Invasive mould infection in immunocompromised children: Pulmonary computed tomography findings from two multicentre paediatric cohorts - Daniel K Yeoh; Derek J Roebuck; Madusha Chandratilleke; Julia E Clark; Adrienne Lam; Rishi S Kotecha; Monica A Slavin; Gabrielle M Haeusler; Christopher C Blyth; Karin A Thursky (CMI Communications)
Background: Invasive fungal disease (IFD) can cause significant morbidity in immunocompromised children. The lung is the most common site for IFD caused by moulds. Timely diagnosis is key to facilitate initiation of appropriate treatment. As clinical manifestations are non-specific, initial diagnosis relies on computed tomography (CT) imaging, yet there are limited recent data documenting imaging changes in paediatric pulmonary IFD. In this study, CT images of children with proven/probable pulmonary IFD from two multi-centre cohorts were assessed to document typical changes, including a comparison between causative pathogens, and to measure reliability of radiological reporting in this context. Methods: Pulmonary IFD cases diagnosed between 2003–2013 and 2017–2020 were identified from two respective Australian multi-centre cohort studies of immunocompromised children. Proven/probable IFD was defined according to the EORTC/MSG definitions. Initial CT images at the time of IFD diagnosis were independently reviewed by two board-certified paediatric radiologists. Presence of EORTC/MSG-defined and other changes was documented. Inter-rater reliability was assessed. Impact of specific imaging features on outcome at 6 months was assessed using multivariate regression. Results: A total of 99 cases were included (65 aspergillosis, 19 non-aspergillus moulds (NAM) and 15 histopathological-mould cases). Median age was 9.6 years (IQR 5.1–13.6); 89.9 % had an underlying haematological malignancy. Nodules (85.4 %), the halo sign (49.5 %) and wedge shaped/segmental consolidation (35.9 %) were the most frequent EORTC/MSG-defined features. Cavitation and air-crescent sign were uncommon. Agreement between radiologists was fair to moderate for most common imaging features. No specific radiological finding differentiated aspergillosis from NAM infection. The presence of mass on initial CT and NAM infection were independently associated with poor outcome. Conclusions: In proven/probable pulmonary IFD in immunocompromised children, nodules with or without halo sign are the most frequent finding. Agreement between radiologists was variable for common imaging features, and specific findings did not correlate with the causative pathogen. Microbiological confirmation remains vital in children with suspected pulmonary IFD.